Gud og samvittigheden. Et tema i Ralph Waldo Emersons prædikener - Nørager, Troels (Dansk Teologisk Tidsskrift, 2018)
Despite the fact that the entire collection of Ralph Waldo Emerson’s sermons was published more than two decades ago, scholarly interest has so far been limited. By focusing on the particular theme of the relation between God and individual conscience, the present article analyzes most of Emerson’s sermons on this particular topic. Emphasizing Emerson’s background in Boston-Unitarianism and his theological debt to William Ellery Channing, it is demonstrated how Emerson already in his sermons cherishes the idea of a living, direct connection between God and the soul. The fact that he inherits from Calvinism the idea of God as moral perfection, leads him to regard the individual’s conscience as the highest faculty and the place where God primarily speaks to man. Conscience also implies an obligation to judge for yourself or having ‘self-trust’, and in this way the sermons reveal the theological roots of the later Emerson’s concept of self-reliance.